Relationships between the motivation of medical tourists and the quality of medical services. (7th August 2020) - Lee, Timothy J.; Lim, Hyunsuk; Kim, Dohee
Abstract: This study aims to: (a) identify the motivation to travel for medical reasons and the quality of the medical services received; and (b) examine the relationship between the quality of medical services and the attitudes held by tourists about these. It fills the gap in the literature by contributing to our knowledge of medical tourists' behavior. A total of 500 questionnaires were distributed at 25 hospitals and travel agencies within Korea. The results deliver insightful messages in the fields of travel behavior and motivation in the medical tourism industry, and for health marketers and planners of medical tourism services.